An efficient hybrid solar and electromagnetic harvesting system for autonomous operation of small sensors - Meddour, Fayçal; Bencherif, Hichem; Boukarkar, Abdelheq; Abdi, Mohamed Amir; Amir, Mounir (Optik (Stuttgart), 2020)
•A combination of solar cells and a rectenna is proposed to realize a solar and electromagnetic energy harvesting system.•SHJ solar cells with a combination of AZO/TiO2 as antireflection coating and a diffraction grating morphology is proposed.•Simulation and experimental results validate that the combined harvesting system is a promising candidate for autonomous sensors operation.•The proposed system can operate regardless of the light intensity to feed some sensors and small devices autonomously. In this study, we propose a combination of solar cells and a rectenna to realize a solar and electromagnetic energy harvesting system. The proposed harvester consists of a circular slot antenna, a rectifier circuit which is designed with a reverse-biased Schottky diode, and SHJ solar cells with a combination of AZO/TiO2 as antireflection coating and a diffraction grating morphology. Each designed component has been characterized through simulations and measurements. First, the solar cells are designed and investigated separately. Then, they are carefully placed near the slot loop antenna, which is attached to the rectifier circuit, to realize the combined harvesting system. The heterojunction solar cells with an intrinsic thin layer (SHJ) have been designed based on light trapping mechanism, which reduces the reflection of solar radiation and interfacial traps effects significantly. Solar cells’ simulations are obtained using an analytical model. The parameters of light trapping, as well as the effects of the position of the solar cells on board of the patch, are studied carefully. Simulation and experimental results validate that the combined harvesting system is a promising candidate for autonomous operation of some sensors and small devices. Indeed, the efficiency of the rectenna is enhanced greatly from 21to 74 % when combined with the solar cells.